Application of Virtual Reality and Robotic Arm - Hsiao-Hui Li; Yuan-Hsun Liao; Chong Xian Wang (Journal of ICT, Design, Engineering and Technological Science, 2019)
There will still be factory accidents in today's life, such as a machine operation inadvertently causing the person crushed to death, the arm twisted, and machine electric leakage caused personnel to be killed by an electric shock. In addition to the above, there are many high-risk and not conducive to manual operation of the environment exists. If you can take a remote control for the robotic arm to replace the work of professional personnel, reduce the occurrence of danger and improve the efβiciency of production. Therefore, this paper explores the use of virtual reality and remote control robotic arm to perform more precise, complex and dangerous work. The design combines a VR device, the multi-axis robotic arm and synchronizing video to VR environment for the user using the head-mounted display and real manipulation operation. We are mainly divided into two parts to discuss. The βirst part is the image synchronization, how to capture the camera image to display on the headset achieved image synchronization. The second part is the synchronization of operation and control, how to perfectly synchronize the robotic arm's movements and the controller to facilitate complex, precise and dangerous operation. Through virtual interaction and stability of the arm, it can reduce the occurrence of errors and improve the accuracy of the calibration. It is hoped that this method can effectively reduce industrial safety accidents.